2015
DOI: 10.4236/cm.2015.61003
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Antineoplastic Pharmacological Effects and Mechanisms of Litchi Seeds

Abstract: Researchers have proven the Litchi seeds of possessing salutary pharmacodynamic effects, such as dispelling cold, relieving pain, promoting the circulation of qi, and removing stasis. This has resulted in its categorization as an affinal drug and diet in the traditional Chinese medicine. Important research progress has been obtained on the chemical components, traditional pharmacological effects, antivirus and antitumor effects, their molecular mechanisms and immune effects of litchi seeds in recent years. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…These results indicated that the inhibitory effect of LCSE on EGFR signaling directly effected the Akt activity, then triggered an intrinsic apoptosis mechanism to induce apoptotic death in both NSCLC cells. A previous report indicated that LCSE also triggers the other extrinsic apoptosis pathway to induce apoptosis [10]. Our results appeared to support this viewpoint, with the level of procaspase 8 being gradually decreased after LCSE treatment in the NSCLC cells.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results indicated that the inhibitory effect of LCSE on EGFR signaling directly effected the Akt activity, then triggered an intrinsic apoptosis mechanism to induce apoptotic death in both NSCLC cells. A previous report indicated that LCSE also triggers the other extrinsic apoptosis pathway to induce apoptosis [10]. Our results appeared to support this viewpoint, with the level of procaspase 8 being gradually decreased after LCSE treatment in the NSCLC cells.…”
Section: Discussionsupporting
confidence: 87%
“…Erk-1/-2 translocates to the nucleus and triggers expression of cell-cycle-controlling proteins. Akt could phosphorylate Bad and dissociate Bad with Bcl-2, which suppresses the activity of Bax and leads to the avoidance of apoptosis in cancer cells [10]. In this study, we demonstrated the elevation of the number of apoptotic cells, and the reduction in mitochondria membrane potential in both treated A549 and NCI-H661cells with LCSE.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Apoptosis occurs as a result of inhibition of expression of the signaling molecule, NF-Κβ followed by decreased expression of p65 unit and finally reduction in the levels of antiapoptoic members of Bcl-2 family. The caspase cascade is activated and expression of Fas protein is stimulated (Zhang and Zhang, 2015). Production and secretion of cytokines, epidermal growth factor (EGF), epidermal growth factor receptor (EGFR), platelet derived growth factor (PDGF) and tumor necrosis factor-α (TNF-α) and inflammatory factors, IL-1, TNF-α, IFN-γ is facilitated by litchi seed extract (Lin et al, 2013;Hsu et al, 2012).…”
Section: Mechanisms Of Anti-cancer Activity Litchimentioning
confidence: 99%